Socialization of Cash Transfers (BLT) and Program Keluarga Harapan (PKH) to Beneficiary in Sambikarto Village Sekampung District - Ahmad Efendi; Astri Setyawati; Dwilita Astuti; Tri Alim (Universitas Nahdlatul Ulama Lampung, 2021)
Community dedication activity aim for educate people about prosedure or requirements of acceptance cash grant (BLT)and PKH for Sambikarto village community to know who deserved cash grant and didn`t in Sambikarto Village Sekampung District. Target of this community dedication activity was people who lived in Sambikarto village, Sekampung District, Lampung Timur. Method was used in this community dedication activity was discourse, direct demonstration, and discussion. Discourse method was used for application about general knowledge about Socialization Cash Grant (BLT) and Program Keluarga Harapan (PKH beneficiary). Demonstration used for provide examples of description and criteria of BLT and PKH beneficiary used existing game and tools. Discussion was used for complete things didn`t accmodated by both method explained before. This guidance involved lectures of social science and humanities faculty (FISH) and headman of Sambikarto Village, Sekampung District, Lampung Timur, that include community around Sambikarto Village. Obstacles faced was people in first time didn`t know who deserved accept cash grant or didn`t of BLT and PKH. Benefit obtained by participants from community dedication activity ini were knowing the differensiation of BLT and PKH and to inform people about socialization BLT and PKH beneficiary in daily activity.